The Influence of Doctors Therapeutic Communication and Nurses Communication Style on the Quality Services for Pregnant Women in Hospitals Deli Serdang - Gumay, Vita Sari; Kurniawati, Dewi; Nurbani (Formosa Journal of Social Sciences (FJSS), 2024)
The maternal mortality rate is the number of women who die during pregnancy (the 42 day period after giving birth). The higher maternal mortality rate, the lowest welfare of a country. The highest MMR in North Sumatra province 2021 was in Deli Serdang district with 23 cases. Therefore, health professional are required to have communication skills with therapeutic meaning. This study aims to analyze the influence of doctors' therapeutic communication and nurses' communication styles on the quality of services for pregnant women in hospitals deli serdang district. This quantitative research uses analytical observational methods with a cross sectional approach. Data collection was conducted on 97 pregnant women who consulted at the polyclinic gynecology and obstetrics at Drs. H. Amri Tambunan Hospital, Grandmed Hospital and Haji Hospital. The data collection technique was carried out by distributing a questionnaire. The results of this study indicate that that doctors' therapeutic communication influences the quality of service at the Deli Serdang district hospital. The nurse's communication style influences the quality of service at the Deli Serdang district hospital. There is an influence of doctors' therapeutic communication and nurses' communication styles on the quality service of hospital at the Deli Serdang district. Has a very strong relationship with a adjusted R square of 73.2%. The remaining 26.8% was influenced by other factors outside this research